2020
DOI: 10.1016/j.jsv.2020.115654
|View full text |Cite
|
Sign up to set email alerts
|

Trailing-edge noise generation from a flat-plate aerofoil interacting with a prescribed vortex

Abstract: Aerodynamic noise generated by aerofoil-vortex interaction has widely been studied in the past where the primary noise source mechanism is the scattering of the vortex at the leading edge (LE) of the aerofoil. In this paper the secondary source mechanism-the subsequent vortical scattering at the trailing edge (TE)-is investigated in detail, which shows that the secondary source mechanism is mainly contributed by nonlinear effects as predicted by some analytical studies in the past. The present study is perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…However, recent evidence may suggest that the trailing edge may contribute appreciably to turbulence-airfoil interaction noise. 108,109…”
Section: Broadband Noisementioning
confidence: 99%
See 1 more Smart Citation
“…However, recent evidence may suggest that the trailing edge may contribute appreciably to turbulence-airfoil interaction noise. 108,109…”
Section: Broadband Noisementioning
confidence: 99%
“…However, recent evidence may suggest that the trailing edge may contribute appreciably to turbulence-airfoil interaction noise. 108,109 In 1975, Amiet published a landmark paper 110 that forms the foundation of leading edge noise prediction to this day. Amiet's approach and its extensions were reviewed by Roger and Moreau, 111 and related to trailing edge noise prediction models.…”
Section: Ingestion Noisementioning
confidence: 99%
“…In this study, a different approach is used based on a frequency filtering of the flow 41 . The advantage is that once the flow field is filtered, it is still possible to analyse its evolution over time and results are not limited to a contour of the modes.…”
Section: Physical Phenomena Identification and Analysismentioning
confidence: 99%
“…The phase inversion arises because its sense of rotation is opposite to that of the initial vortex. The existence and significance of secondary vorticity in aerofoil noise 415 generation were first recognised by [32] in a fundamental numerical study of leading edge noise due to flat plates. In [32] it was shown that secondary vorticity is induced as a result of nonlinear interactions between the aerofoil and the impinging vortex.…”
mentioning
confidence: 99%
“…The existence and significance of secondary vorticity in aerofoil noise 415 generation were first recognised by [32] in a fundamental numerical study of leading edge noise due to flat plates. In [32] it was shown that secondary vorticity is induced as a result of nonlinear interactions between the aerofoil and the impinging vortex. This secondary vortex then convects towards the trailing edge and was a significant source of trailing edge noise.…”
mentioning
confidence: 99%